Effect of specific retention biomaterials for ball attachment on the biomechanical response of single implant-supported overdenture: A finite element analysis - Gibreel Mona; Sameh Ahmed; Hegazy Salah; Närhi Timo O; Vallittu Pekka K; Perea-Lowery Leila (Netherlands, 2022)
Abstract
Purpose
The purpose of this finite element analysis (FEA) was to evaluate the effect of specific retention biomaterials with different elastic modulus on the biomechanical response to the axial and off-axial biting loads of a mandibular midline single implant-supported overdenture (SIO) model.
Methods
Five 3-dimensional (3D) finite element models of an edentulous mandible with SIO were designed as follows: model M with a titanium retentive element for ball attachment, model P with a PEEK retentive element, model S with a silicone resilient liner retentive element, model T with a thermoplastic acrylic resin retentive element made from a CAD-CAM material, and model A with a polyacetal resin retentive element. Posterior bilateral vertical load (PV) at the 1st molar areas and anterior oblique load (AO) at the incisal edge of the mandibular central incisors at a 30-degree angle of 100 N were applied. Stress values were recorded.
Results
Stress values were higher for all models under (AO) loading than under (PV) loading. Model M recorded the highest stress values on the implant, its components, cortical, and cancellous bone under both loading conditions. Under (AO) loading condition, the ball abutment von Mises stress value in model S was almost 7 times lower than that of model M (19 and 130 MPa respectively) and the other 3 models (P, T, and A) (119, 121, and 120 MPa respectively). However, model S recorded the highest value of denture base stress at the attachment area.
Conclusions
The elastic modulus of retention materials can affect stresses generated on the implant overdenture components and supporting structures.